Practical guidelines for online Narrative Exposure Therapy (e-NET) – a short-term treatment for posttraumatic stress disorder adapted for remote delivery. Issue 1 (1st January 2021) - Kaltenbach, Elisa; McGrath, Patrick J.; Schauer, Maggie; Kaiser, Elisabeth; Crombach, Anselm; Robjant, Katy
ABSTRACT: Background : Online therapy has become increasingly desirable and available in recent years, with the current COVID-19 pandemic acting as a catalyst to develop further protocols enabling therapists to conduct online treatment safely and efficaciously. Offering online treatment potentially means that treatments are available to clients who would otherwise have no access, closing the gap in the provision of mental health services worldwide. Objective : This paper focuses on practical guidelines using online Narrative Exposure Therapy (e-NET). It aims to be an addition to the general manual of NET to enable therapists to deliver online treatment. The face-to-face version of NET is a well-known short-term and evidence-based treatment for posttraumatic stress disorder; e-NET is currently being tested in several additional trials. Methods : The differences between NET and e-NET are elaborated and depicted in detail. Results : Difficulties encountered in e-NET delivery, e.g. confidentiality, dealing with interruptions, comorbid symptoms among others, are similar to those that occur during face to face interventions but the solutions have to be adapted. Dissociation is often regarded as a challenge in face-to-face treatment, and requires particular attention within the online setting. Therefore, tools for addressing dissociation in this particular setting are presented. Conclusions : These practical guidelines show the advantages as well as the challenges therapists face when conducting e-NET. They aim to empower therapists working with trauma clients to conduct e-NET confidently and safely. HIGHLIGHTS: Therapists need more practical tools how to conduct trauma therapy online. Differences between face-to-face NET and online NET are elaborated. Safety measures and practical information about how to conduct e-NET are provided.